Uncertainty Model For Quantitative Precipitation Estimation Using Weather Radars - Gómez Vargas, A. Ernesto; Obregón N., Nelson; Álvarez Pomar, C. Lindsay (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
This paper introduces an uncertainty model for the quantitatively estimate precipitation using weather radars. The model considers various key aspects associated to radar calibration, attenuation, and the tradeoff between accuracy and radar coverage. An S-band-radar case study is presented to illustrate particular fractional-uncertainty calculations obtained to adjust various typical radar-calibration elements such as antenna, transmitter, receiver, and some other general elements included in the radar equation. This paper is based in “Guide to the expression of Uncertainty in measurement” [1] and the results show that the fractional uncertainty calculated by the model was 40 % for the reflectivity and 30% for the precipitation using the Marshall Palmer Z-R relationship.
Keywords: quantitative precipitation estimation; radar measurements; uncertainty; weather radar; IJIMAI